Integration of Gender Equity and Social Inclusion (GESI) in the Agroforestry Project on Trees Outside the Forest in India (TOFI) - Bohra, Babita (CIFOR-ICRAF, 2023)
The benefits derived from the expansion of trees outside forests (TOF) can vary greatly for women, men and other socially diverse groups due to their distinct roles, responsibilities, and access to resources like land and trees. Therefore, it is essential to ensure the meaningful participation of both women and men from diverse social and economic backgrounds in these initiatives. Additionally, interventions should be tailored to address their specific needs and interests to achieve an equitable distribution of benefits. Climate mitigation and restoration efforts often overlook gender considerations, resulting in unequal outcomes and reinforcing inequalities. A genderresponsive strategy promotes inclusive participation, fair benefit distribution and social equality. The Centre for International Forestry Research-World Agroforestry (CIFOR-ICRAF) and a consortium of partner organizations are implementing TOFI, a joint project of USAID and the Ministry of Environment, Forestry, and Climate Change that aims to ensure that women and social groups are meaningfully included in TOFI’s efforts to increase the area under the trees outside forests in India. To achieve its objectives, the project, which is currently in the implementation stage, is creating TOF innovation platforms, which make it easier to map value chains, markets and policies. To adapt the project to the specific characteristics of seven states, a comprehensive geographic gender assessment is conducted, providing a deeper understanding of gender dynamics in forestry and agroforestry projects. Assessment findings reveal valuable insights for gender mainstreaming in this field.